1968
DOI: 10.1192/bjp.114.508.265
|View full text |Cite
|
Sign up to set email alerts
|

The Effects that Patients Have on their Families in a Community Care and a Control Psychiatric Service—A Two Year Follow-up

Abstract: The effects that mentally ill people have on their families have been more commented upon than studied. The currently favoured practice of community care has increased the need for a systematic attempt to evaluate the families' problems, and an opportunity to do this occurred when a community psychiatric service was introduced in Chichester in 1958, while the neighbouring Salisbury district continued with a conventional hospital-based service. The Medical Research Council's Clinical Psychiatry Research Unit ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
0
14

Year Published

1974
1974
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(109 citation statements)
references
References 9 publications
8
87
0
14
Order By: Relevance
“…Six mois après leur congé de l'hôpital, on a réévalué les patients en utilisant les méthodes et mesures suivantes: 1) la SCRS; 2) la REHAB; 3) l'inventaire Oregon sur la qualité de vie (OQULI); 4) le nombre de fois qu'un patient a été admis à l'hôpital dans les six mois suivants son congé (Récidive); 5) la durée de l'hospitalisation (en jours) au cours de ces six mois (Durée); 6) la Family Burden Scale de Grad et Sainsbury (1968); 7) l'émotion exprimée (EE), en utilisant le Five Minute Speech Sample (Magana et al, 1986); et 8) les coûts et les bénéfices pour la société, six mois après le congé de l'hôpital.…”
Section: La Collecte Des Donnéesunclassified
“…Six mois après leur congé de l'hôpital, on a réévalué les patients en utilisant les méthodes et mesures suivantes: 1) la SCRS; 2) la REHAB; 3) l'inventaire Oregon sur la qualité de vie (OQULI); 4) le nombre de fois qu'un patient a été admis à l'hôpital dans les six mois suivants son congé (Récidive); 5) la durée de l'hospitalisation (en jours) au cours de ces six mois (Durée); 6) la Family Burden Scale de Grad et Sainsbury (1968); 7) l'émotion exprimée (EE), en utilisant le Five Minute Speech Sample (Magana et al, 1986); et 8) les coûts et les bénéfices pour la société, six mois après le congé de l'hôpital.…”
Section: La Collecte Des Donnéesunclassified
“…Grad and Sainsbury (1968) and Robins, Copas and Freeman-Browne (1979) suggested that time may be a moderate factor -perhaps families learn to cope through experience. Noh and Turner (1987) found that families that have adequate social support and feel in control of their life circumstances experience less psychological distress related to the relative's illness than do families that do not have many resources.…”
Section: The Balance and Adaptationmentioning
confidence: 99%
“…O n a mis en relief, depuis la «désinstitutionnalisation», que les familles représentaient une des principales sources de soutien pour les personnes atteintes de troubles mentaux majeurs (Grad et Sainsbury, 1968;Guberman et al, 1991;McElroy, 1987a;Thompson et DoIl, 1982). Des études britanniques, canadiennes et étatsuniennes ont montré, en effet, qu'une bonne proportion des personnes présentant un problème sérieux de santé mentale vivent avec leur famille ou sont en contact avec elle sur une base régulière (Carpentier et al, 1992;Grad et Sainsbury, 1968;Gibbons et al, 1984;St-Onge et Lavoie, 1987, 1994Solomon et al, 1986;Thompson et DoIl, 1982).…”
unclassified
“…Des études britanniques, canadiennes et étatsuniennes ont montré, en effet, qu'une bonne proportion des personnes présentant un problème sérieux de santé mentale vivent avec leur famille ou sont en contact avec elle sur une base régulière (Carpentier et al, 1992;Grad et Sainsbury, 1968;Gibbons et al, 1984;St-Onge et Lavoie, 1987, 1994Solomon et al, 1986;Thompson et DoIl, 1982).…”
unclassified